THE IMPLEMENTATION OF IPAS (NATURAL SCIENCE AND SOCIAL STUDIES) IN ELEMENTARY SCHOOL: LEARNING PLOT AND TEACHER CONSIDERATION - Hanum, Citra Bahadur; As'ary, Yasin; Komariah, Mia; Maftuh, Bunyamin (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
The policy IPAS (science and social studies) is a new phenomenon in education. This study aims to determine the implementation and considerations of teachers in carrying out IPAS learning. This research involved fourth-grade teachers at an elementary school in Bandung City. The method used is a case study with a qualitative approach. The instruments used are interviews, observation, and documentation studies. Data analysis uses the Miles and Huberman technique. The results showed that the teacher's efforts to plan, use the elements, and determine the plot specifically in IPAS learning with consideration to the student's needs, the effectiveness and efficiency of time, facilities and infrastructure, suitability of materials and elements, there are the differences felt by the teacher in the form of challenges as well as solutions that found. In conclusion, science learning is not a thematic or integrated learning process, but linked or connected because of some of the material in the book and the flow of learning objectives where science is more dominant and social studies is a support, and vice versa. These findings can be utilized as a reference and consideration in making policies and implementing science learning for other schools.